PENERAPAN DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS PESERTA DIDIK KELAS VIII.2 SMPN 13 PEKANBARU - Ira Yustika; Rini Dian Anggraini; Maimunah (Jurnal Ilmiah Matematika Realistik, 2026)
This study aims to improve the mathematical understanding skills of class VIII.2 students of SMPN 13 Pekanbaru through the application of the model.Discovery Learning matter theorem Pythagoras The research subjects were 42 students, 17 male and 25 female. The type of research was Classroom Action Research (CAR) consisting of two cycles, each cycle consisting of four stages: planning, implementation, observation, and reflection. The instruments used were learning devices and data collection instruments. The results of the study showed that the application of the learning model Discovery Learning can improve students' mathematical comprehension skills. This is demonstrated by the increase in Mathematical Understanding Ability (MUA) scores in each cycle. In the initial test, the KPM score increased from 51.19 to 73.6 in cycle I, and to 83.55 in cycle II. Based on this, the application of the model Discovery Learningcan improve the mathematical understanding ability of class VIII.2 students of SMPN 13 Pekanbaru in the odd semester of the 2025/2026 academic year.